Enhancing MSME Capacity in Preparing Financial Statements for Accessing Financing - Purba, Jamian; Djatnicka, Erlina Widayanti; Wulandari, Dian Sulistyorini; Rachman, Mutiara Arvia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of Micro, Small, and Medium Enterprises (MSMEs) significantly contributes to Indonesia's economic growth, yet many MSMEs face challenges in accessing financing due to inadequate financial reporting capabilities. This community service project, aimed to bridge this gap by equipping MSME owners with the skills and knowledge to prepare standardized financial statements. Conducted from October 14 to October 28, 2024, the program utilized a participatory, hands-on approach tailored to the unique challenges faced by MSMEs. The training sessions covered the preparation of Income Statements, Balance Sheets, and Cash Flow Statements, combining theoretical insights with practical applications. The results revealed that 80% of participants successfully prepared complete financial statements by the program's conclusion, demonstrating significant improvement in their financial literacy and reporting skills. However, 20% of participants required additional guidance in specific areas, such as cash flow analysis and transaction classification. Participant feedback highlighted high satisfaction with the program’s relevance and practicality, with suggestions for introducing digital financial tools in future sessions.